Out-of-Plane and In-Plane Magnetization Behavior of Dipolar Interacting FeNi Nanoislands around the Percolation Threshold. (27th November 2016) - Stupakov, A.; Bagdinov, A. V.; Prokhorov, V. V.; Bagdinova, A. N.; Demikhov, E. I.; Dejneka, A.; Kugel, K. I.; Gorbatsevich, A. A.; Pudonin, F. A.; Kovaleva, N. N.
Abstract : Magnetic properties of inhomogeneous nanoisland FeNi films were studied by SQUID magnetometry. The FeNi films with nominal thickness ranging from 0.6 to 2.0 nm were deposited by rf sputtering on Sitall glass substrates and covered by a protecting Al2 O3 layer on the top. The SQUID data indicate pronounced irreversibility behavior for the out-of-plane temperature-dependent magnetization response (measured atH ≃ 100  Oe) using zero-field cooling (ZFC) and field-cooled warming (FCW) after the applied dc magnetizing fieldH m ≃ 2  T for the FeNi samples with nominal thickness 1.1 nm≲ d ≲ 1.8  nm, below the percolation threshold. The positive difference between the FCW and ZFC data identifies two irreversibility temperature scales, T B ≈ 50  K andT ⁎ ≈ 200  K, which can be associated with the superparamagnetic and superferromagnetic behavior in inhomogeneous nanoisland FeNi films, respectively. However, above the film percolation threshold, we observed a crossover from the out-of-plane to in-plane magnetization orientation. Here, the in-plane FCW-ZFC difference implies negative remanent magnetization response in the temperature rangeT B ≲ T ≲ T ⁎ . The observed magnetization properties can be associated with the presence of the superferromagnetic phase in self-assembled clusters of quasi-2D metallic magnetic FeNi nanoislands.